Women’s experiences of using vaginal trainers (dilators) to treat vaginal penetration difficulties diagnosed as vaginismus: a qualitative interview study - Macey, Kat; Gregory, Angela; Nunns, David; das Nair, Roshan (BioMed Central, 2015)
Background